Randomised controlled trials for informing perinatal care - Gale,C; McGuire,W; Juszczak,E (Neonatology, 2020)
BACKGROUND: Randomised controlled trials provide the best evidence for the effects of interventions and are a key tool in the effort to improve the care and outcomes for newborn infants. METHODS: We discuss the role of randomisation for minimising selection bias in clinical trials and describe examples of seminal trials that have shaped the development of modern perinatal care. We consider the challenges inherent in designing and delivering large, simple, and pragmatic trials, and the need for the development and adoption of core outcome sets to ensure that trials provide high-quality evidence of sufficient validity and applicability to guide policy and practice. RESULTS: Since the earliest days of modern neonatology, the randomised controlled trial has been recognised as the best method for assessing treatments and practices. While many strategies that reduce mortality and morbidity have been introduced following randomised trials, there are, however, important examples of ineffective or potentially harmful practices that have been adopted in the absence of trial-based evidence. Typically, randomised controlled trials in perinatal care need to recruit several thousand participants to be able to detect modest but potentially important effects of new interventions on the most important but rare outcomes. Given the concerns about the financial burden and regulatory complexity of standard trial designs, innovative "efficient" trial designs are being evaluated to streamline processes while safeguarding participants. CONCLUSIONS: Well-conducted randomised controlled trials provide the most robust evaluation of interventions aimed at improving outcomes for newborn infants and their families. Increasingly, these trials will need to be large and multicentre (often international) and use a simple and pragmatic protocol, incorporating meticulous follow-up procedures and assessment of long-term outcomes.